2018
DOI: 10.3382/ps/pey167
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cecal microbiome of selected high and low feather-pecking laying hens

Abstract: In mammals, it has become increasingly clear that the gut microbiota influences not only gastrointestinal physiology but also modulates behavior. In domestic birds, ceca have the greatest gastrointestinal microbial population. Feather-pecking (FP) behavior in laying hens is one of the most important unsolved behavioral issues in modern agriculture. The aim of the present study was to assess the cecal microbial community of divergently selected high (HFP; n = 20) and low (LFP; n = 20) feather-pecking birds at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 38 publications
7
39
0
Order By: Relevance
“…Comparisons of the cecal microbiomes between layer lines divergently selected for FP or with different actual FP behavior revealed apparent differences [11][12][13]. It is difficult to determine, whether these differences are a cause for FP or just a consequence of feather consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of the cecal microbiomes between layer lines divergently selected for FP or with different actual FP behavior revealed apparent differences [11][12][13]. It is difficult to determine, whether these differences are a cause for FP or just a consequence of feather consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Even if studies on livestock are still uncommon, they have all implicated the gut microbiota in host behavior (109)(110)(111)(112)(113). In hens, the aggressive damaging behavior of feather pecking was associated higher relative abundances of Clostridiales and a lower relative abundance of Lactobacillus in the luminal microbiota composition of ileum, caecum and colon sections combined (114,115). In humans, Parashar and Udayabanu (94) have reviewed the relationships between specific bacteria populations and both stress and anxiety.…”
Section: Streptococcus D14mentioning
confidence: 99%
“…Overall, it seems both host genetic variations and intestinal microbiota composition could explain variations in individual Salmonella Enteritidis carriage in chicken. Furthermore, genetic studies on other phenotypic traits, such as digestive e ciency [22], body weight [23] or feather-pecking in laying hens [24] showed that host genetic variations in uence the intestinal microbiota composition in chicken. In these studies, authors identi ed several QTLs and single nucleotide polymorphisms (SNPs) associated with speci c bacterial species that may explain the phenotype and calculated heritabilities of these bacteria abundances.…”
Section: Introductionmentioning
confidence: 99%